ANALYSIS OF GOOD CORPORATE GOVERNANCE, LEVERAGE, AND COMPANY SIZE AGAINST PROFIT MANAGEMENT - Sukarni Crystianty Suhaili; Vargo Christian L. Tobing (SEAN Institute, 2023)
The study aims to examine the effect of Good Corporate Governance, Leverage and company size on profit management in manufacturing sector companies listed on the Indonesia Stock Exchange in 2017 – 2021. This research is a quantitative study with a data collection method using purposive sampling to obtain results that match the criteria. Based on the predetermined criteria, a total sample of 23 companies with a research period of 5 years was obtained, so that 115 samples were obtained. However, there were 38 outlier data in this study, bringing the sample tested to 77 samples. This study used SPSS 25 in analyzing the data. The results of this study show that managerial ownership affects profit management , while institutional ownership and an independent board of commissioners have no effect on profit management. These three variables are variants used to test Good Corporate Governance. Furthermore, the variable leverage has a positive and significant effect on profit management and the size of the company has a negative and significant effect on profit management. Also obtained, managerial ownership, institutional ownership, independent board of commissioners, leverage and size The company exerts an influence on profit management.